Success Rate of Assisted Reproductive Technology Treatment at a Tertiary Fertility Centre in Nepal - Shrestha Pradhan, Sanu Maiya; Karki, Anita; Pradhan, Renee; Vaidya, Dijan; Dhital, Rolina (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To determine the success rate of various Assisted Reproductive Technology (ART) treatments at a tertiary fertility centre in Nepal. Methods: This study was a retrospective study conducted at Creator’s IVF Nepal Pvt. Ltd. (CIVF) from November 2015 till April 2020. The success rates of ART treatment were preclinical pregnancy rate, clinical pregnancy rate, and live birth rate. Anonymised information about demographic and clinical characteristics of the patients, ART treatment related variables, and ART outcome related variables were collected from the medical records. Descriptive analysis was performed using SPSS (Statistical Package for the Social Sciences) version 20. Results: Overall, 768 ART cycles leading up to embryo transfer were analysed. About 69.6% of all ART treatments were autologous cycles followed by oocyte recipient cycles (22.0%), and embryo recipient cycles (8.4%). About 88.7% were fresh embryo transfers whereas 11.3% were frozen embryo transfers. Overall the preclinical pregnancy rate, clinical pregnancy rate and live birth rate were 48.4 %, 43.3%, and 33.3% respectively. Conclusions: The success rates of ART treatment in this study were comparable to the international estimates. More research on treatment outcomes by all ART service providers in Nepal is needed to provide better evidence on utilization and efficacy of ART treatment in fertility centres across the country. Keywords: assisted reproductive technology; clinical pregnancy; in-vitro fertilization; live birth; success rate